Working With Geospatial and Descriptive Data in A Geoinformation System - Jo’rayev Vohid Tojimamatovich; Axmadjonova Mohidil Hotamjon qizi (Periodica Journal, 2022)
In this article, the users who are studying geoinformatics have an opinion about the scientific application of the geoinformation system, its use in geodesy, cartography, land resources management and other fields in the field of geoinformatics. In addition, the article focuses on increasing the skills of data input, processing, storage and representation in the form of spatial data, which are considered the main tasks of the field of geoinformatics.
Keywords: Information; space photo; GAT; geodata